Weather Shocks, Age of Marriage and the Direction of Marriage Payments - Lucia Corno; Nicole Hildebrandt; Alessandra Voena (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
In this paper, we examine the impact of variation in local economic conditions on the hazard into child marriage (i.e. prior to age 18) among young women in Africa and India. We show that rainfall shocks, a major source of income variation in these areas, have similar effects on crop yields but opposite effects on the early marriage hazard in the two regions: in Africa, droughts increase the hazard into early marriage, while in India, droughts decrease the hazard. We argue that the differential impact of drought on the marriage hazard can be explained by differences in the direction of traditional marriage payments in each region (bride price in Africa and dowry in India). Our results highlight the importance of understanding the relationship between prevailing cultural norms and household responses to economic shocks; as we show here, differences in prevailing customs can result in dramatically different household responses to aggregate income fluctuations..
Keywords: J1; O15; 330; Income shocks; informal insurance; marriage; Africa; India; dowry; bride